Habilidades metafonológicas y decodificación lectora de estudiantes del segundo grado de primaria de una institución educativa del Callao - Quille Soto, María Elena (2012)
The present study tries to determine the relation between the skills metafonológicas and the reading decodificación. The participants are 86 pupils of the second degree of primary of an Educational Institution of the Callao, with ages between 7 and 8 years. There applied the test of skills to himself metalingüísticas (THM) of Gómez, Valero, Buadas and Perez adapted by Panca (2000) and the subtest of decodificación reading of the exploratory test of specific dyslexia (PEDE) proposed by Condemarín and adapted by Arrieta (2010). The investigation is of type correlacional and the sample is of available type. The results show that a significant correlation exists between the skills metafonológicas of syllabic segmentation and the reading decodificación. Also relation exists between the syllabic suppression and the reading decodificación though this one is low.Other skills metafonológicas as the detection of heaps, syllabic addition, to isolate phonemes, to join phonemes and to count phonemes did not present any correlation with the reading decodificación.